Peran Wardrobe Dan Make Up Dalam Persiapan Syuting Film Sabda Rindu - Bila, Salsa; Edlina, Ria (CV. ITTC INDONESIA, 2024)
This final assignment report was prepared based on the author's experience during the film making project entitled